Self Control and Religiosity Towards Free Sex Behavior Adolescent in Surabaya - Sukesi Sukesi; Ervi Husni; Evi Pratami (Alliance oh Health Activists (AloHA), 2018)
Background: Adolescent free sex and the incidence of premarital pregnancy from year to year are increasing. The causes include lack of implementation of consequent religion, lack of supervision of adolescents, lack of moral understanding in adolescent relationships and the influence of external cultural norms. The purpose of this study is to analyze the effect of Self Control and Religiosity on adolescent free sex. Method: This study used Analitic Design with Cross Sectional approach. The sample in this study were some teenagers in Kawung I Middle School and Surabaya MTsN I, the sample size is 260 students, with the Propotional Stratifield Sampling technique. Data collection instrument using questionnaire, the independent variable is Self control and Religiosity, the dependent variable is free sex, with the analysis of Linear Regression test. Results: Self control affects the knowledge of young women about free sex, the value of p = 006, affects the attitude with a value of p = 0.007 and influences the practice of adolescent free sex, with a value of p = 0.011. Religiosity affects the knowledge of young women about free sex, the value of p = 001, influences attitudes with p = 0,000 and influences the practice of adolescent free sex. with a value of p = 0.019 Conclusion: Self control and Religiosity significantly influence adolescent free sex. The higher the level of self control and religiosity, then adolescent free sex become more lower. Keywords: self control, religiosity, free sex